THE CUSTOMS UNION: HOW IT AFFECTS THE PRIORITIES OF KAZAKHSTAN’S ECONOMIC POLICY - RAKHMATULINA, Gulnur (CENTRAL ASIA AND THE CAUCASUS, 2011)
Kazakhstan has been a member of the Customs Union (CU) for more than a year now. This has inevitably affected how its economy functions and given rise to a broad public discussion of the prospects for this kind of integration union, its advantages, and its possible detriment to the country’s economic development. During the first year of its life, the Customs Union had a relatively positive impact on Kazakhstan’s economy. However, what real advantages does Kazakhstan business gain from the CU? First, reciprocal trade barriers among its participating states have been removed. Customs registration at the internal borders of the CU was cancelled on 1 July, 2010. Moreover, the tax agencies of the CU states now communicate electronically and regularly exchange information from commodity import statements and regarding indirect tax payment by taxpayers. Participants in foreign trade transactions can get up to a 50-day deferment on VAT and excise tax payments. All of this stimulates the expansion of economic trade ties among the CU participating states and helps to boost their reciprocal goods turnover. Kazakhstan’s trade volume with the CU countries in 2010 increased by 28.1% and amounted to almost 20% of the republic’s total goods turnover.1 The total amount of value added tax receipts on imports from the Russian Federation between 1 July, 2010 and 31 December, 2010 amounted to 91.2 million tenge, which is 1.2-fold more than for the corresponding period of 2009. VAT on imports from the Republic of Belarus between 1 July, 2010 and 31 December, 2010 amounted to 3.7 million tenge, which is 1.3-fold more than for the corresponding period of 2009.2 On 1 July, 2011, customs control is transferred from the internal borders of the CU to the periphery of the participating states, which will also promote further development of reciprocal trade among them.